Operation, Administration and Maintenance Capabilities of the AT&T 5ESS Switch - Charles D. Gavrilovich; Robert A. Multra; and Wayne L. Wang (Tongxin xuebao)
The AT&T 5ESSTM switch is a time-division digital switching system designed to provide telecommunications services for an extensive range of applications: local, toll, international gateway, and operator services. The 5ESS switch system is designed to provide cost-effective, flexible and reliable mechanization and centralization of maintenance and administrative functions. This paper describes the operation, administration and maintenance （OA&M） features of the export 5ESS switch. The emphasis is on the features that reduce training costs and result in maintenance savings over the life-cycle of the 5ESS switch.The OA&M capabilities are a fundamental part of the 5ESS switch design. They provide monitoring and control of the system, even during overload conditions. The exchange is capable of detecting errors by the use of self-checking hardware, and software which audits data throughout the exchange. Diagnostic and testing functions may be run on demand, by schedule, or executed as a result of an error threshold being exceeded. Extensive trunk and line maintenance capabilities are also integrated into the exchange. Flexibility is provided in the recording and reporting of test results and status information.OA&M capabilities are designed to evolve to support new features and services as they are introduced on the 5ESS switch. User control of OA&M functions allows flexible application of operation and maintenance strategies which can improve exchange performance and reduce costs.